From Melville to Saunders: Using Liminality to Uncover US-American Racial Fantasies - Seuberth, Lisa (COPAS : Current Objectives of Postgraduate American Studies, 2022)
This paper offers a comparative reading of Herman Melville’s romance Moby Dick (1851) and George Saunders’s fantastic ghost story Lincoln in the Bardo (2017), tracing the reverberations of Toni Morrison’s ‘American Africanism’ as a specific kind of White supremacist discourse in both novels. After sketching nineteenth-century romance and recent fantasy literature as liminal genres fitting for a critical negotiation of the equally liminal Africanist presence, this paper shows how both novels employ liminality as a shared narrative strategy to transport their criticism on White supremacy and anti-Blackness.<br
Keywords: American Africanism; White supremacy; nineteenth-century romance; twenty-first century fantasy; Whiteness; anti-Blackness; liminality